Inspecting Zara's Advertisement Campaign amidst Gaza Conflict and Its Global Backlash - Nisa, Rahmatun; Aini, Azka Nurul; Syahriyani, Alfi (Muslim English Literature, 2024)
This study investigates the controversial Zara advertisement campaign released during the Gaza conflict and analyzes its global backlash. Using Kress and Van Leeuwen’s visual theory, the research explores its representational, interpersonal, and compositional dimensions. Text findings reveal that representationally, the advertisement features culturally significant symbols: a white cloth signifying death in Palestinian culture and a kaffiyeh symbolizing resistance. Interpersonally, it positions viewers as passive observers, evoking discomfort, and pity, while textually, it emphasizes symbolic representation with stark contrasts and strategic framing. The advertisement’s release during heightened tensions led many to perceive it as exploitative and culturally insensitive, despite some defenses of artistic expression. Public reactions, particularly on social media, highlighted the ethical challenges of such campaigns. The study questions the campaign for violating Corporate Social Responsibility (CSR) principles by disregarding ethical considerations and societal well-being. It underscores the importance of cultural sensitivity in global marketing, advocating for ethical advertising that respect global diverse audiences.